Perbedaan Profil Stigma Masyarakat Tentang Pasien Gangguan Jiwa Di Wilayah KerjaAntara Puskesmas Wates Dengan Puskesmas Gedongan kota Mojokerto - AKBAR, AMAR; MUJIATI, LILIS (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractPatients who are suspected of suffering from mental disorders more done by the family by means of penyasungan, after all efforts of medical treatment performed by the family. Patients with mental disorders often get stigma from the surrounding environment. Stigma is attached to schizophrenic patients and their families. Stigma is also one of the inhibiting factors in the healing of client mental disorders. This study aims to determine the stigma of people about mental disorders patients in the area or work between Puskesmas Wates with Puskesmas Gedongan. The research design used in this study is comparative. The sample in this study amounted LO 121 Head of Family with Cluster Sampling technique. The instrument used is a community stigma questionnaire about mental patients with 40 statements. Chi Square statistic test showed that p (0,003) <.1 (0,05) so that JIO rejected mean there is difference of society stigma about mental patient in working area between Puskesmas Wates and Puskesmas Gedongan. Negative stigma that occurs in the community working area Puskesmas Wates because in the area there are already mental health programs so that people are more able to accept the condition of people who have mental disorders. While in the community in the working area of Puskesmas Gedongan health center has a positive stigma because in the area there is no mental health program.Keywords: CJ.fHN, Mental Disorders, Stigma